2019
DOI: 10.7150/ijbs.36532
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA CircEZH2 Suppresses Transmissible Gastroenteritis Coronavirus-induced Opening of Mitochondrial Permeability Transition Pore via Targeting MiR-22 in IPEC-J2

Abstract: Transmissible gastroenteritis (TGE) is a contagious and infectious disease that is characterized by severe vomiting and diarrhea of swine , especially piglet, and caused by transmissible gastroenteritis coronavirus (TGEV) . TGEV infection provokes mitochondrial damage of porcine intestinal epthelial cell (IPEC), which is responsible for inflammation and cell death. In our previous study, we have demonstrated that circular RNA circEZH2 was down-regulated during TGEV infection and promoted the activation of nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…By activating NF-κB pathway, IL-6 inhibited mPTP opening, while HK2 had no significant impact on the activation of NF-κB pathway. The authors concluded that two pathways including circEZH2/miR-22/ IL-6/NF-κB axis and circEZH2/miR-22/HK2 axis are involved in regulating TGEV-induced mPTP opening [57].…”
Section: Regulatory Role Of Circrnas In Transmissible Gastroenteritis Coronavirus (Tgev) Infectionmentioning
confidence: 99%
“…By activating NF-κB pathway, IL-6 inhibited mPTP opening, while HK2 had no significant impact on the activation of NF-κB pathway. The authors concluded that two pathways including circEZH2/miR-22/ IL-6/NF-κB axis and circEZH2/miR-22/HK2 axis are involved in regulating TGEV-induced mPTP opening [57].…”
Section: Regulatory Role Of Circrnas In Transmissible Gastroenteritis Coronavirus (Tgev) Infectionmentioning
confidence: 99%
“…Retrograde transcriptional signaling of mitochondria plays vital role as stress sensors to adapt its environment 25 . The retrograde signals between mitochondria and nucleus, including ATP, ROS, UPR mt , 2-hydroxyglutarate, opening of mitochondrial permeability transition pore, can regulate gene expression in the nucleus 26 , 27 . Recently, a potential link between mitochondrial stress and widespread changes in chromatin structure has been proposed 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of circEZH2 in IPEC-J2 cells inhibited TGEV-induced mitochondrial permeability transition pore (mPTP) opening via attaching miR-22 to regulate hexokinase 2 (HK2) and interleukin 6 (IL-6), while silencing of IL-6 supressed activation of NF-κB pathway. This study provides potential drug targets for the prevention and treatment of TGE ( Zhao et al, 2019b ). Studies have also examined circRNA expression profiles by using high-throughput sequencing in MBDK cells infected with bovine viral diarrhea virus (BVDV) ( Li et al, 2019 ) and in the silkworm following bombyx mori nuclear polyhedrosis virus (BmNPV) infection ( Hu et al, 2018 ).…”
Section: Circrnas Associated With Virus Infectionmentioning
confidence: 99%
“… CircRNA Effect on virus Regulated pathway Refer-ence circ_0000479 Overexpression promotes the expression of RIG-I and hampering HTNV replication circ_0000479/ miR-149-5p/ RIG-I pathway ( Lu et al, 2020 ) hsa_circ_0004812 Knockdown expression promotes the IFN-α/β, and inhibits HBV replication. circ_0004812/ miR-1287-5p/ FSTL1 axis to regulate IFN-induced immune response ( Zhang and Wang, 2020 ) circRNA_100338 Overexpression enhanced migratory and invasive ability of cancer cells circRNA_100338 / miR-1413p axis to regulate invasive potential in liver cancer cells ( Huang et al, 2017 ) circ-GATAD2A Knockdown expression enhances autophagy and inhibits IAV H1N1 replication, reverse after overexpression circ-GATAD2A/ VPS34-dependent autophagy pathway ( Yu et al, 2019 ) circ-Vav3 Overexpression induces EMT, promote ALV-J related tumorigenesis circ-Vav3/gga-miR-375/YAP1 axis induces EMT pathway ( Zhang et al, 2019 ) circEZH2 Overexpression inhibits TGEV-induced mPTP opening and regulate NF-κB activation circEZH2/ miR-22/ HK2 axis, circEZH2 /miR-22/IL-6/ NF-Kb pathway to regulate mPTP opening ( Zhao et al, 2019b ) …”
Section: Circrnas Regulate Viral Replication and Induce Antiviral Immmentioning
confidence: 99%
See 1 more Smart Citation